IMPLEMENTASI METODE TREND MOMENT UNTUK PREDIKSI PENJUALAN (STUDI KASUS DI TOKO ZACOZI PANCING KABUPATEN SOLOK) - Fauziyyah, Atika (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2024)
Zacozi Fishing Shop is a shop that sells various kinds of fishing equipment, from small to large. Through direct research at the Zacozi Pancing Shop, the problem was found that from year to year sales of fishing equipment at this shop experienced an erratic increase and decrease in sales every month. This happens because many goods are not sold out and there are many goods that consumers need but the stock of goods requested by consumers is insufficient. This is also because the shop does not have a system that can predict sales, so many products are not available for a long time. Therefore, it is necessary to have a sales prediction information system using the Trend Moment method to be able to predict sales of goods in the following month. The data used is fishing rod sales data from June 2022 to June 2023. With a sales prediction system using the Trend Moment method which can produce sales predictions for goods at the Zacozi Pancing Shop with an average success rate of 90%, it can help the shop in picking Actions that should be taken, especially in controlling product availability using the Trend Moment method so that stock shortages and excesses can be avoided.